The in-vivo diuretic activity of methanolic extract of Quercus leucotrichophora A. Camus seeds - Shivali Singla; Chinu Kumari; Abhishek Soni; Sachin Goyal (Elsevier, 2022)
Introduction: Traditional healers' assertions that Quercus leucotrichophora A. Camus is a plant that has been used in traditional medicine to treat various urinary and renal diseases, thus the present study aims to investigate the diuretic activity of the methanolic extract of seeds in rats. Methods: Dried course powder was extracted with methanol using soxhlet extraction. Male Wistar rats were given a control (normal saline, 15 ml), a reference medication (furosemide, 13 mg/kg), and three separate doses (250 mg/kg, 375 mg/kg, and 500 mg/kg) of the extract orally. Urine volume, urinary electrolytes, urine pH, and conductivity were measured to establish the extract's diuretic activity. The urine outflow was tested at 6, 12, and 24 h, as well as electrolyte content, pH, and conductivity. Creatinine, urea, aldosterone, and electrolyte concentrations in plasma and urine samples were also determined. The index kidney function was determined by analyzing kidney homogenate. One-way ANOVA was used to evaluate the data. Results: The findings demonstrated that the extract increased diuresis in a dose-dependent manner, i.e., at 500 mg/kg, the extract exhibited significant diuretic effects (p < 0.001) as compared to the reference medicine, furosemide. The urinary excretion of Na+, K+, and Cl− was also significantly increased (p < 0.001) at all doses. The effectiveness of the extract as a diuretic was further established by biochemical analysis. These results confirm the historic usage of the herb as a diuretic and the importance of maintaining indigenous knowledge. Conclusion: Collectively, the data provided here indicated that using a methanolic extract of Quercus leucotrichophora seeds to cause diuresis is a viable option.